The Global Economic Crisis and G20 Summit of April 2009: a Step Forward Towards Better Global Governance or Global Government? - Florin Bonciu (Romanian Journal of European Affairs, 2009)
The paper analyzes the implications of the current global economic crisis for the decision-making mechanisms and interactions among the major players. The analysis explores the possibility that the changes implied and required by the economic crisis may lead either to better global governance or even a step closer to a possible, virtual, global government. The latter hypothesis is approached in a different way as compared to similar topic papers in the sense that a possible global government is seen as a long term objective result of the various reactions and solutions taken by individual entities.